The Median Effective Dose of Ciprofol Combined with Sufentanil for Inhibiting Responses to Gastroscope Insertion in Obese Patients: A Prospective, Single-Center Study - Xue Z; Liu X; Qian W; Yang N; Pan Y; Zhou Y; Jiang W; Li F; Qian B (Drug Design, Development and Therapy)
Zhouya Xue,1,2,* Xiang Liu,1,2,* Weisheng Qian,1 Nan Yang,1 Yongyi Pan,1 Yong Zhou,1 Wei Jiang,1 Feng Li,1 Bin Qian1 1Department of Anesthesiology, The First People’s Hospital of Yancheng, The Yancheng Clinical College of Xuzhou Medical University, Yancheng, Jiangsu, People’s Republic of China; 2Jiangsu Province Key Laboratory of Anesthesiology, Jiangsu Province Key Laboratory of Anesthesia and Analgesia Application Technology, NMPA Key Laboratory for Research and Evaluation of Narcotic and Psychotropic Drugs, Xuzhou Medical University, Xuzhou, Jiangsu, People’s Republic of China*These authors contributed equally to this workCorrespondence: Feng Li, Department of Anesthesiology, The First People’s Hospital of Yancheng, No. 166 West Yulong Road, Yancheng, Jiangsu, 224001, People’s Republic of China, Email 1226637852@qq.com Bin Qian, Department of Anesthesiology, The First People’s Hospital of Yancheng, No. 166 West Yulong Road, Yancheng, Jiangsu, 224001, People’s Republic of China, Email qbmzk19@sina.comBackground: Ciprofol, a recently developed intravenous anesthetic, whereas sufentanil is a widely used adjuvant for gastroenteroscopy sedation. The recommended dosage of ciprofol for obese patients remains unclear. Our study aimed to determine the median effective dose (ED50) of ciprofol in combination with sufentanil for obese patients undergoing gastroscopy sedation.Methods: A total of 70 patients undergoing painless gastroscopy from July 2024 to September 2024 were recruited. Patients were assigned to the obese group (body mass index [BMI]≥ 28 kg/m2, n=34) and non-obese group (18.5 kg/m2 ≤BMI< 24 kg/m2, n=36). All patients received 0.1 μg/kg of sufentanil, and the ciprofol dose was determined by the modified Dixon sequential method with an initial dose of 0.4 mg/kg and a dose gradient of 0.01 mg/kg. The dose of ciprofol administered to the subsequent patient was determined by the response of the preceding patient. The response referred to the patient’s cough, swallowing, and body movement during gastroscope insertion. The primary outcome was the ED50 of ciprofol in each group, while the secondary outcomes comprised the incidences of hypoxemia, hypotension, bradycardia, postoperative nausea and vomiting (PONV), and hemodynamic parameters.Results: The ED50 of ciprofol was 0.278 mg/kg (95% confidence interval [CI]: 0.226– 0.297 mg/kg) in the obese group and 0.347 mg/kg (95% CI: 0.329– 0.360 mg/kg) in the non-obese group for gastroscopy sedation. The ED50 of ciprofol in the obese group was significantly lower than that in the non-obese group (P< 0.05). The incidence of hypoxemia in the obese group was significantly higher than that in the non-obese group (P< 0.05).Conclusion: Obesity affected the ED50 of ciprofol, suggesting that the ciprofol dosage should be adjusted in obese patients.Keywords: obesity, ciprofol, median effective dose, painless gastroscopy